Built from Below. - Guillery, Peter (Taylor & Francis, 2010)
Extending the concept of British vernacular architecture to embrace buildings such as places of worship, villas, hospitals, suburban semis and post-war mass housing, this book is of use to anyone with an interest in architectural history.